TBIO-10. PEDIATRIC TARGETED THERAPY 2.0: DEVELOPMENT OF PERSONALIZED PEDIATRIC ONCOLOGY. Issue 2 (22nd June 2018) - Ecker, Jonas; Selt, Florian; Sahm, Felix; Capper, David; Korshunov, Andrey; Grund, Kerstin; Dikow, Nicola; Sutter, Christian; van Tilburg, Cornelis; Witt, Hendrik; von Deimling, Andreas; Jones, David T W; et al.
Abstract: Precise diagnosis and robust detection of actionable alterations is required for individualized treatments. The Pediatric Targeted Therapy (PTT) 2.0 program aims at improvement of diagnostic accuracy and detection of targetable alterations by extended molecular diagnostics. The impact of these analyses on clinical management is being evaluated. Pediatric patients with relapsed or progressive tumors after treatment according to standard protocols are included, independent of the histological diagnosis. Formalin fixed paraffin embedded material and a blood sample for germline correction are requested. The methods employed are DNA methylation array, customized targeted gene panel sequencing (130 genes), RNA and Sanger sequencing in selected cases, and immunohistochemistry (IHC) of selected markers. A questionnaire-based follow-up is used to determine the clinical impact of the analysis. We have included n=111 cases from 22.02.2017.-31.12.2017, analysis was completed for n=83 cases (75%) at the time of abstract submission. The most common entities were brain tumors (n=56/83, 67%). DNA methylation array alone allowed diagnostic classification in n=45/83 cases (54.2%) and n=34/56 brain tumor cases (60, 7%), respectively. Actionable targets as detected by copy number calculation, gene panel sequencing, RNA sequencing and IHC were found in n=47/83 cases (56.6%). Pathogenic germline alterations with clinical relevance were identified in n=7/83 cases (8.4%) and were confirmed by Sanger sequencing. Follow-up analyses are ongoing. In conclusion, combination of next-generation diagnostics such as methylation arrays and targeted sequencing in addition to selected IHC markers added robust information concerning diagnosis and targetable alterations. The impact on clinical decision-making and on outcome is currently being evaluated.